RETRACTED: Sustainable development and social investment strategies as an element of the SDGS - Bortnik Artem; Lisin Anton; Niyazbekova Shakizada; Turdiyeva Zukhra; Varzin Vasiliy; Tsurova Lisa; Ugurchiev Omar (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001